2011
DOI: 10.1007/s00401-011-0895-y
|View full text |Cite
|
Sign up to set email alerts
|

Inner ear lesions in congenital cytomegalovirus infection of human fetuses

Abstract: Congenital cytomegalovirus (CMV) infection is the leading cause of non-hereditary congenital sensorineural hearing loss (SNHL). The natural course and the pathophysiology of inner ear lesions during human fetal CMV infection have not yet been reported. Inner ear lesions were investigated in six CMV-infected fetuses aged 19-35 postconceptional weeks and correlated with central nervous system (CNS) lesions. All the fetuses had high viral loads in the amniotic fluid and severe visceral and CNS lesions visible by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 36 publications
6
69
0
2
Order By: Relevance
“…Autopsied pediatric CMV cases confirmed that cytomegalic cells were present in the inner ear; lesions were mainly observed in the endolymphatic compartment of the inner ear, particularly in the vestibular structures. [13][14][15][16][17][18][19][20] Little research has been carried out on vestibular disorders induced by congenital CMV, and only 2 studies are available. 21,22 Zagólski 21 suggests that the prevalence of vestibular disorders is probably underestimated and could be higher than that of hearing loss.…”
Section: What This Study Addsmentioning
confidence: 99%
See 3 more Smart Citations
“…Autopsied pediatric CMV cases confirmed that cytomegalic cells were present in the inner ear; lesions were mainly observed in the endolymphatic compartment of the inner ear, particularly in the vestibular structures. [13][14][15][16][17][18][19][20] Little research has been carried out on vestibular disorders induced by congenital CMV, and only 2 studies are available. 21,22 Zagólski 21 suggests that the prevalence of vestibular disorders is probably underestimated and could be higher than that of hearing loss.…”
Section: What This Study Addsmentioning
confidence: 99%
“…To date, routine inner ear investigations of these infants include classic audiometric follow-up but not vestibular testing despite strong evidence of vestibular infection. 13,16 In addition, congenital and earlyonset complete vestibular loss are known to induce severe delays in the acquisition of the first posturomotor milestones, such as the ability to hold the head stably and to sit and walk independently. 23,24 The main objective of this study was to determine the prevalence, severity, and changes over time of vestibular deficits in pediatric CMV cases and their correlation with other sensorineural disorders induced by CMV infection.…”
Section: What This Study Addsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two recent studies on terminated fetuses have extended our knowledge about congenital HCMV infection of the inner ear. 133,134 Inflammatory cells mainly composed of activated CD8 1 T lymphocytes were more abundant in the inner ear structures, where the virus was detected within stria vascularis followed by Reissner's membrane. Inflammatory cells were also found along cochlear nerve fibers and in the spiral ganglion.…”
Section: Sensorineural Hearing Loss Due To Congenital CMV Infectionmentioning
confidence: 99%